Artificially designed ferroelectromagnetic superlattices by laser molecular beam epitaxy - Yang, Zhen (2013)
Transition metal oxides have attracted great attention for decades because of their interesting physics and various promising properties, such as high temperature superconductivity, ferroelectricity and ferromagnetism. Many commercial electronic devices have been made, for instance, superconducting Josephson junction, ferroelectric random access memory (FeRAM), piezoelectric sensors, actuators and transducers. Thus, recently there has been resurgence for their very interesting physical properties of “multi- ferroicity”, which offers both electric and magnetic parameters to play with. Furthermore, an additional degree of freedom, manipulation of spin by ferroelectric polarization, has been exhibited via magnetoelectric coupling. To conduct magnetoelectric coupling in epitaxial layers, it is required to grow aligned hetero-interfaces at atomic scales. In the present research work, attempts of realizing magnetoelectricity are made for laser molecular beam epitaxial grown single crystalline multiferroic superlattices. To achieve these artificially designed superstructures, alternative layers of ferromagnetic and ferroelectric have been grown in nanometers thickness. Finally, the fully strained multiferroic superlattices are successfully realized by growing mixed valence manganite and barium titanite as layered superstructures.